Fascial dehiscence after radical cystectomy: Is abdominal exploration mandatory? - Paz Lotan; Shayel Bercovich; Daniel Keidar; Kamil Malshy; Ziv Savin; Rennen Haramaty; Jonathan Gal; Jonathan Modai; Dan Leibovici; Roy Mano; Barak Rosenzweig; Azik Hoffman; et al. (BMC Urology, 2022)
Abstract Background Fascial dehiscence after radical cystectomy may have serious clinical implications. To optimize its management, we sought to describe accompanying intraabdominal findings of post-cystectomy dehiscence repair and determine whether a thorough intraabdominal exploration during its operation is mandatory. Methods We retrospectively reviewed a multi-institutional cohort of patients who underwent open radical cystectomy between 2005 and 2020. Patients who underwent exploratory surgery due to fascial dehiscence within 30 days post-cystectomy were included in the analysis. Data collected included demographic characteristics, the clinical presentation of dehiscence, associated laboratory findings, imaging results, surgical parameters, operative findings, and clinical implications. Potential predictors of accompanying intraabdominal complications were investigated. Results Of 1301 consecutive patients that underwent cystectomy, 27 (2%) had dehiscence repair during a median of 7 days post-surgery. Seven patients (26%) had accompanying intraabdominal pathologies, including urine leaks, a fecal leak, and an internal hernia in 5 (19%), 1 (4%), and 1 (4%) patients, respectively. Accompanying intraabdominal findings were associated with longer hospital stay [20 (IQR 17, 23) vs. 41 (IQR 29, 47) days, P = 0.03] and later dehiscence identification (postoperative day 7 [IQR 5, 9] vs. 10 [IQR 6, 15], P = 0.03). However, the rate of post-exploration complications was similar in both groups. A history of ischemic heart disease was the only predictor for accompanying intraabdominal pathologies (67% vs. 24%; P = 0.02). Conclusions A substantial proportion of patients undergoing post-cystectomy fascial dehiscence repair may have unrecognized accompanying surgical complications without prior clinical suspicion. While cardiovascular disease is a risk factor for accompanying findings, meticulous abdominal inspection is imperative in all patients during dehiscence repair. Identification and repair during the surgical intervention may prevent further adverse, possibly life-threatening consequences with minimal risk for iatrogenic injury.